Effects of interactions between aspergillus oryzae extract (Amaferm) and antimicrobial compounds on the growth of ruminal bacteria - Beharka, A.A.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effect of Amaferm, with or without antimicrobial compounds, was determined on the growth rate of pure cultures of predominant ruminal bacteria. Adding Amaferm to media containing chlortetracyline or neomycin tended to diminish the negative effects of those compounds on the growth rate of some ruminal bacteria, even when they had shown no positive response to Amaferm alone. However, adding Amaferm to media containing tylosin decreased the growth rate of Selenomonas ruminantium D. These results indicate that Amaferm interacts both positively and negatively with certain antimicrobial compounds.
Keywords: Beef; Aspergillus oryzae extract; Rumen bacteria; Antimicrobial compounds